Curdione induces ferroptosis mediated by m6A methylation via METTL14 and YTHDF2 in colorectal cancer - Fang Wang; Zheng Sun; Qunyao Zhang; Hao Yang; Gang Yang; Qi Yang; Yimiao Zhu; Wenya Wu; Wenwen Xu; Xiaoyu Wu (BMC, 2023)
Abstract Background Curdione is a sesquiterpene isolated from Curcumae Rhizoma that possesses high biological activity and extensive pharmacological effects. As a traditional Chinese medicine, Curcumae Rhizoma can inhibit the development of many types of cancer, especially colorectal cancer. However, the anti-colorectal mechanism of its monomer curdione remains unclear. Methods Colorectal cancer (CRC) cells were treated with curdione at doses of 12.5 μM, 25 μM, and 50 μM, and then the cells' activity was measured with methyl thiazolyl tetrazolium (MTT). Nude mice were administered different doses of curdione subcutaneously and oxaliplatin by tail vein injection, and then hematoxylin-eosin (HE) staining was adopted to examine tumor histology. Moreover, flow cytometry was applied to detect reactive oxygen species in cells and tissues. Kits were employed to detect the levels of iron ions, malondialdehyde, lipid hydroperoxide, and glutathione. Polymerase chain reaction (PCR) and Western blotting were adopted to detect ferroptosis and m6A modification-related factors. A methylation spot hybridization assay was performed to measure changes in overall methylation. SLC7A11 and HOXA13 were measured by MeRIP-qPCR. The shRNA-METTL14 plasmid was constructed to verify the inhibitory effect of curdione on CRC. Results A dose-dependent decrease in activity was observed in curdione-treated cells. Curdione increased the accumulation of reactive oxygen species in CRC cells and tumor tissues, greatly enhanced the levels of malondialdehyde, lipid hydroperoxide and Fe2+, and lowered the activity of glutathione. According to the qPCR and Western blot results, curdione promoted the expression of METTL14 and YTHDF2 in CRC cells and tissues, respectively, and decreased the expression of SLC7A11, SLC3A2, HOXA13, and glutathione peroxidase 4. Additionally, in animal experiments, the curdione-treated group showed severe necrosis of tumor cells, as displayed by HE staining. Furthermore, compared with the control group, levels of m6A modifying factors (namely, SLC7A11 and HOXA13) were increased in the tissues after drug intervention. METTL14 knockdown was followed by an increase in CRC cell activity and glutathione levels. However, the levels of reactive oxygen species, malondialdehyde, and iron ions decreased. The expression levels of SLC7A11, SLC3A2, HOXA13, and GPX4 were all increased after METTL14 knockdown. Conclusion The results suggest that curdione induces ferroptosis in CRC by virtue of m6A methylation.